Ground testing of a 1% gravo-aeroelastically scaled additively-manufactured wind turbine blade with bio-inspired structural design. (April 2020) - Kaminski, Meghan; Loth, Eric; Griffith, D. Todd; Qin, Chao (Chris)
Abstract: A gravo-aeroelastic scaling (GAS) method is developed to design wind turbine blades that represent centrifugal, aerodynamic, and gravitational loads of extreme-scale turbines. To match these elements, certain blade characteristics are given priority: non-dimensional 1st flap-wise frequency, non-dimensional flapping tip deflection, and tip-speed-ratio. Using the GAS method, a 1% sub-scale blade was designed to match the mass distributions and ground tested to match the non-dimensional flap-wise dynamics and deflections of Sandia National Lab's 13.2-MW blade. To the authors' knowledge, this is the first manufactured blade model to employ gravo-aeroelastic scaling using additive manufacturing and bio-inspiration. A series of scale models were designed, built, and ground-tested using weights consistent with scaled steady rated load conditions of an extreme-scale turbine. The models designed were evolved to increase gravo-elastic scaling performance by employing lightweight bio-inspirational morphology and carbon fiber reinforcements. The final version has non-dimensional gravo-elastic errors as follows: 3% in total mass, 15.6% in deflection from ground-based loads representing full-scale steady rated conditions, and 8.1% in the first flap-wise modal frequency (when normalized by the scaled rpm for rated conditions). This model demonstrates the GAS concept can be applied to manufacture sub-scale models as small as 1% of an extreme-scale rotor blade. Graphical abstract: Image 1 Highlights: A 1/100th gravitational and elastically scaled wind turbine blade is developed. The model is developed using additive manufacturing and bioinspiration. The scaling errors are 3% for mass, 16% for tip deflection and 8% for flap-wise frequency.